Walt Whitman : words for America - Kerley, Barbara; Selznick, Brian (New York : Scholastic Press, 2005)
A biography of the American poet whose compassion led him to nurse soldiers during the Civil War, to give voice to the nation's grief at Lincoln's assassination, and to capture the true American spirit in verse.
G8
Keywords: Whitman, Walt, -- 1819-1892 -- Juvenile literature; Whitman, Walt, -- 1819-1892.; Poets, American -- 19th century -- Biography -- Juvenile literature; Nurses -- United States -- Biography -- Juvenile literature; Poets, American; Nurses; United States -- History -- Civil War, 1861-1865 -- Medical care -- Juvenile literature; United States -- History -- Civil War, 1861-1865.